Peningkatan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Problem Based Learning Pada Materi Sistem Tata Surya - Dara Ninggar A; Elia Ling Ling (Lembaga Bale Literasi, 2023)
This study aims to determine the increase in student learning outcomes in the science subject on Earth and the Solar System for class VII H Semester II at SMP N 2 Tengaran by using the Problem Based Learning (PBL) model. This research is a Classroom Action Research conducted in 2 cycles. The research subjects were students in class VII H of SMP Negeri 2 Tengaran Even Semester 2022/2023 Academic Year, a total of 34 students. Data collection was carried out by learning achievement tests and observations. The data that has been collected is then analyzed using a qualitative descriptive analysis technique. From the results of the analysis it was found that the learning outcomes of students experienced an increase, namely, cycle I (58%) and cycle II (88%). The conclusion from this study is that the Problem Based Learning (PBL) learning model has a positive influence on improving the learning outcomes of class VII H students on Earth and the Solar System at SMP N 2 Tengaran.